2017
DOI: 10.1021/jacs.6b12764
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Rate Constants and Turnover Frequency in Nucleic Acid-Templated Reactions: Reaching Terminal Velocity

Abstract: Nucleic acid-templated reactions have attracted significant attention for nucleic acid sensing and imaging. The level of signal amplification obtained from templated reactions is a function of the template turnover, wherein the template acts as the catalyst. Herein, we report the application of a pyridinium linker that immolates upon photocatalytic reduction with a ruthenium complex to yield the fastest nucleic acid templated reaction reported to date. We show that the templated reaction turnover is limited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 35 publications
3
90
0
Order By: Relevance
“…We reasoned that our system could be extended to proceed at low substrate concentration, if an overhang sequence was adjacent to the catalyst for substrate hybridization. We had previously shown that a pentamer PNA was sufficient for PNA–PNA templated reactions . This was achieved using a bifunctional bipyridine bearing a carboxylic acid group at the 5‐position and a Fmoc‐protected glycine conjugated to the 5′‐amino group (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reasoned that our system could be extended to proceed at low substrate concentration, if an overhang sequence was adjacent to the catalyst for substrate hybridization. We had previously shown that a pentamer PNA was sufficient for PNA–PNA templated reactions . This was achieved using a bifunctional bipyridine bearing a carboxylic acid group at the 5‐position and a Fmoc‐protected glycine conjugated to the 5′‐amino group (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that the photocatalytic activity of [Ru(bpy) 3 ] 2+ type of complexes can be harnessed to reduce different immolative linkers, enabling substrate turnover with only one reagent exchanging on the template. However, these studies clearly point to the fact that substrate turnover is rate limiting . Alternatively, a templated reaction could be used to generate an active catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Expectedly, k app significantly increased for norbornene 14mer‐ 15 , the most reactive dienophile used in this study, to the highest herein determined values ( k app [10 −4 s −1 ]=[22±1] to [46±3]). The determined k app values are in accordance with reported first order rate constants for DNA‐templated reactions . The half‐lives ranged from 46±6 min (14mer‐ 11 ) to 2.5±0.9 min (14mer‐ 15 ) in DA inv with 29mer‐ g1 as template (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…The 5‐mer PNA was inserted in a beacon architecture composed of an 8‐mer l ‐γ‐PNA for DNA recognition and a 5‐mer d ‐γ‐PNA to ensure sufficient specificity for nucleic acid sensing. The interaction with sub‐stoichiometric DNA template and light irradiation at 455 nm induced hairpin opening and triggered photocatalytic reduction of the pyridinium linker …”
Section: Uncaging Of Smart Probes For Nucleic Acid Imagingmentioning
confidence: 99%